Defining Nocturnal Polyuria in Adolescents - Tasmia Promi; Anthony Brooks; Gulzhan Tologonova; Marie-Claire Roberts; Sarita Dhuper; Meseret Tena; Oluwatoyin Bamgbola; Monique Hanono; Jeffrey P. Weiss; Karel Everaert; Tine DeBacker; Thomas F. Monaghan; et al. (Continence)
Nocturnal polyuria (NP) is a leading cause of nocturia in adults. While diagnostic criteria for NP have been established in adult men, they have not been validated in other demographic groups including women, adolescents, and children, and little is known about appropriate reference values in these populations. Accordingly, the present study aimed to determine an hourly nocturnal urine production (NUP) rate in adolescents most predictive of the presence of nocturia. We analyzed prospectively collected data of 100 male and female adolescents aged 10-18 years. All subjects completed nocturnal voiding diaries and significant nocturia was defined as ≥1 or more voids per night. Receiver operating characteristic (ROC) curves were used to test the performance of different NUP values in predicting nocturia. On ROC, the area under curve (AUC) was 0.85. On multivariable logistic regression with variables of sex, obesity, and elevated blood pressure, adding NUP as a categorical variable maximally increased the predictive value of the model upon utilizing a cutoff of 50 ml/h, increasing the R2 from 0.491 to 0.683. A NUP >50 ml/h had a sensitivity of 62.2% and a specificity of 96.4% in predicting nocturia. A cut-off value of NUP >50 ml/h may be relevant to the clinical management of adolescents with nocturia.